The Undefeated Defeat - Yunita, Fenny Tria; Prasetyo, Hery; Rosa, Dien Vidia (University of Jember, 2023)
This study critically examines the existence of indigenous peoples within the framework of promoting cultural rights in Indonesia. The main reason for this study is that the Indonesian Law on Advancement of Culture enacted in 2017 did not explicitly include indigenous peoples as a crucial aspect of preserving cultural activities. Consequently, there has been no significant policy reform from the Indonesian government to maintain the rights and existence of indigenous peoples, primarily their cultural rights. From a human rights perspective, culture shapes indigenous peoples' collective identity and political force, hence Indonesia is responsible for protecting and fulfilling their collective rights. Based on the discourse analysis, this study examines two questions: First, to what extent does the recognition of indigenous peoples in the Law on the Promotion of Culture ensure the promotion of the cultural rights of indigenous people? Secondly, what government policies are directed to fulfill indigenous peoples' rights? The finding of this study is that the partial recognition of cultural rights for indigenous peoples affected the undisputable conflicts surrounding sacred rites, which affected the promotion of the collective identity of indigenous people. Keywords: Cultural rights, Identity, Indigenous politics, Land, Marginalization